Metabolic syndrome and cerebrovascular impairment in Alzheimer's disease. (5th March 2015) - Viticchi, Giovanna; Falsetti, Lorenzo; Buratti, Laura; Luzzi, Simona; Bartolini, Marco; Acciarri, Maria Cristina; Provinciali, Leandro; Silvestrini, Mauro
Abstract : Objective: Metabolic Syndrome (MeS) has inconstantly been associated with cognitive impairment. The aim of this study was to investigate the influence of MeS on cerebrovascular reactivity and the possible consequences on cognitive impairment in patients with Alzheimer's disease (AD). Methods: A total of 162 AD patients were enrolled and grouped depending on the presence/absence of MeS. An ultrasound assessment of the neck vessels was performed to evaluate common carotid artery intima‐media thickness (IMT). Cerebral hemodynamics was assessed by the transcranial Doppler‐based breath‐holding index (BHI) test. The relationship between BHI and MeS was explored first with a nested binary logistic model and then with a general linear model/adjusted model. Both models were corrected for sex, age, education, BMI, smoking attitude, and IMT treated as covariates. Results: Pathologic BHI values were significantly more frequent among patients with MeS (risk ratio (RR):1.477; 95% CI: 1.177–1.848). MeS significantly improved the prediction of a pathologic BHI in the binary logistic model (odds ratio (OR):11.64; 95% CI: 1.001–135.304; p  < 0.05). Moreover, AD patients affected by MeS had significantly lower mean Mini‐Mental State Evaluation values than the unaffected ones (16.06; 95% CI: 14.96–17.15 vs 17.79; 95% CI: 17.05–18.53; p  < 0.0001). Conclusions: Our data show an association between the presence of MeS and cerebral hemodynamics. The possibility that a cluster of potentially treatable vascular risk factors may influence AD patients' prognosis deserves consideration. Copyright © 2015 John Wiley & Sons, Ltd.